Multi-Criteria Assessment for Defining Compatible New Use: Old Administrative Hospital, Kyrenia, Cyprus - Vehbi, Beser Oktay; Gunce, Kagan; Iranmanesh, Aminreza (Mdpi, 2021)
It is common for the original use of heritage buildings to become obsolete which in some cases can result in them becoming vacant and subject to deterioration. Adaptive reuse is an essential policy for achieving sustainability as it keeps a continuous building life cycle and avoids building destruction. It is one approach to sustainability where it retains the tangible and intangible values, resilience of the original building materials, and reduces waste and time. The decision-making criteria for compatible new use includes several criteria that affect sustainable development: economic, environment, social, legislative, and architecture. Several Multi-Criteria Decision Making (MCDM) methods have been established in order to aid the process of cultural heritage preservation. This research aims to present an assessment model to support the establishment of appropriate new use by employing an Analytic Hierarchy Process (AHP). The decision-making software used was Expert Choice 11. The administrative hospital in Kyrenia, Cyprus, was selected as the case study in this research. Using the application of AHP with the participation of different stakeholders (experts and locals), a more compatible use as a community centre is proposed and supported by the research methodology.
Keywords: compatible use; historic building; multiple selection criteria; decision-making; AHP